1999
DOI: 10.1021/ja9826542
|View full text |Cite
|
Sign up to set email alerts
|

Host−Guest Chemistry in a Urea Matrix:  Catalytic and Selective Oxidation of Triorganosilanes to the Corresponding Silanols by Methyltrioxorhenium and the Urea/Hydrogen Peroxide Adduct

Abstract: The oxidation of silanes to silanols, catalyzed by methyltrioxorhenium (MTO), proceeds in high conversions and excellent selectivities in favor of the silanol (no disiloxane product) when the urea/hydrogen peroxide adduct (UHP) is used as oxygen source instead of 85% aqueous H 2 O 2 . It is proposed that this novel Si-H oxidation takes place in the helical urea channels, in which the urea matrix serves as host for the silane substrate, the H 2 O 2 oxygen source, and the MTO metal catalyst as guests. In this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 54 publications
4
65
0
Order By: Relevance
“…1). is an effective oxidant in the olefin epoxidation over MTO with [17] or without [10], [11] support materials. By using MTO/Nb 2 O 5 catalyst with UHP as oxidant, a 100% selectivity to epoxide was also obtained (entry 8 [18]).…”
Section: Characterization Of Mto/zrpp Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…1). is an effective oxidant in the olefin epoxidation over MTO with [17] or without [10], [11] support materials. By using MTO/Nb 2 O 5 catalyst with UHP as oxidant, a 100% selectivity to epoxide was also obtained (entry 8 [18]).…”
Section: Characterization Of Mto/zrpp Catalystmentioning
confidence: 99%
“…Several efficient methods have been developed to avoid the side reaction. For example, urea hydrogen peroxide adduct (UHP) with helical channel supposed to serve as a host confined stabilizing environment for MTO was adopted as oxidant in the organic reaction medium, e.g., dichloromethane (CH 2 Cl 2 ) [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that a urea/hydrogen peroxide complex is a very effective oxidant in heterogeneous olefin epoxidations and silane oxidations catalyzed by MTO. [11] With NaY-zeolite as host for these reactions also resulted in high yields and excellent product selectivities. [12] MTO has also been supported on silica functionalized with polyether tethers.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Silanes are classically converted into silanols using strong oxidizing agents such as osmium tetroxide, [3] permanganate, [4] ozone, [5] peracids, [6] or peroxides. [7] However, under these reaction conditions, significant amounts of siloxanes and toxic by-products are formed. To overcome these drawbacks, catalytic systems involving water and oxygen have been recently devised.…”
mentioning
confidence: 99%